2022
DOI: 10.2147/ijgm.s382234
|View full text |Cite
|
Sign up to set email alerts
|

CENPO is Associated with Immune Cell Infiltration and is a Potential Diagnostic and Prognostic Marker for Hepatocellular Carcinoma

Abstract: Purpose To examine the expression, clinical significance, and potential regulatory mechanism of centromere protein O (CENPO) in hepatocellular carcinoma (HCC). Methods CENPO expression in pan-cancer was studied using the TCGA-GTEx database, in HCC and normal liver tissues using the GEO and TCGA databases, and in clinical HCC samples by RT-qPCR. The diagnostic value of CENPO was assessed using receiver operating characteristic curves. Univariate and multivariate regressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…41 G2M checkpoint had a significant effect on cell proliferation, especially tumors. [42][43][44] Stabilizing Snail1 could regulate metastasis and chemoresistance of triple-negative breast cancer by. 45 MKI67 and MMPs could promote the progress of tumor, were the potential biomarker for clinical examination of malignant characteristics in tumors.…”
Section: Discussionmentioning
confidence: 99%
“…41 G2M checkpoint had a significant effect on cell proliferation, especially tumors. [42][43][44] Stabilizing Snail1 could regulate metastasis and chemoresistance of triple-negative breast cancer by. 45 MKI67 and MMPs could promote the progress of tumor, were the potential biomarker for clinical examination of malignant characteristics in tumors.…”
Section: Discussionmentioning
confidence: 99%
“…To date, the utility of SEs in targeting strategies for human tumor therapy has been poorly studied [29] . CENPO has been reported to be elevated in various human tumors, including gastric cancer, hepatocellular carcinoma, bladder cancer [ 16 , 30 , 31 ], and is positively associated with poor prognosis, suggesting that CENPO may affect the response to chemotherapy and immunotherapy. However, the prognostic impact of CENPO on LUAD is still unclear.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that the expression of CENP-O is low in normal tissues, but high in cancer tissues (He et al, 2022;Wang et al, 2023). To evaluate the signi cance of CENP-O in ovarian cancer, we rst used qPCR to examine the expression levels of CENP-O across ve different ovarian cancer cell lines against normal ovarian cell lines IOSE80.…”
Section: Cenp-o Is Upregulated In Ovarian Cancer Cell Linesmentioning
confidence: 99%